KANDUNGAN KIMIA DAN DIMENSI SERAT AKAR, CABANG DAN BATANG BAGIAN ATAS KAYU GMELINA DAN KAYU JATI DI HUTAN RAKYAT SULAWESI SELATAN (PERENNIAL, 2007)
The wood species used in this research was gmelina wood from community forest, Maros Regency and jati wood from community forest, Barru Regency. For objective of the research, parts of the tree were taken a short cut (5 cm) from root, branch and top of the tree. All samples were tested their chemical component (cellulose, hemicellulose, lignin and extractives) and fiber dimensions with it’s derivates fiber. The results showed that root, branch and top of the tree of gmelina wood and jati wood from community forest can be used as a raw material for pulp and papers.Key words: Chemical content, Fiber Dimension, Gmelina Wood, Jati Wood, Community Forest